(untitled) (Research, Society and Development, 2020)
Brazil has numerous species of forage plants, among them the corn crop stands out for its high potential of nutritional value in comparison to other forage plants. The aimed of this study was to evaluate the bromalogical composition of corn silage added with cassava and Embaúba leaves with different level of substitution in the Western Amazon region. Five types of silage were used: SME0 - 100 corn silage and 0% cassava and embaúba, SME25 - 75% corn silage and 25% cassava and embaúba silage, SME50 - 50% corn silage and 50% silage of cassava and embaíba, SME75 - 25% corn silage and 75% cassava and embaúba silage and SME100 - 0% corn silage and 100 cassava and embaúba silage, in a completely randomized design (CRD), with five treatments and five replications. The material was ensiled in silos of plastic tubes for 42 days to guarantee the fermentation process. The pH parameters, dry matter (DM), crude protein (CD), acid detergent fiber (ADF), neutral detergent fiber (NDF), hemicellulose (HEM) and total digestible nutrients (TDN) parameters were evaluated. The data were analyzed using the SISVAR statistical package (P<0.05). The results showed that the silages presented satisfactory bromatological levels in all treatments, being able to be used in the diet of ruminants, with emphasis on the treatments SME50 and SME75 for presenting better values in terms of bromatological characterization.